Clinical and Genetic Features of Biallelic Mutations in SORD in a Series of Chinese Patients With Charcot-Marie-Tooth and Distal Hereditary Motor Neuropathy - Liu, Xiaoxuan; He, Ji; Yilihamu, Mubalake; Duan, Xiaohui; Fan, Dongsheng (Frontiers in Neurology, 2021)
Biallelic mutations in the sorbitol dehydrogenase (SORD) gene have recently been found to be one of the most frequent causes of autosomal recessive axonal Charcot-Marie-Tooth (CMT2) and distal hereditary motor neuropathy (dHMN). This study was performed to explore the frequency of SORD mutations and correlations of the phenotypic-genetic spectrum in a relatively large Chinese cohort. In this study, we screened a cohort of 485 unrelated Chinese patients with hereditary neuropathy by using Sanger sequencing, next generation sequencing, or whole exome sequencing after PMP22 duplication was initially excluded. SORD mutation was identified in five out of 78 undiagnosed patients. Two individuals carried the previously reported homozygous c.757 delG (p.A253Qfs*27) variant, and three individuals carried the heterozygous c.757delG (p.A253Qfs*27) variant together with a second novel likely pathogenic variant, including c.731 C>T (p.P244L), c.776 C>T (p.A259V), or c.851T>C (p.L284P). The frequency of SORD variants was calculated to be 6.4% (5/78) in unclarified CMT2 and dHMN patients. All patients presented with distal weakness and atrophy in the lower limb, two of whom had minor clinical sensory abnormalities and small fiber neuropathy. Our study provides further information on the genotype and phenotype of patients with SORD mutations.